Lower urinary α‐Klotho is associated with lower angiotensin‐(1‐7) and higher blood pressure in young adults born preterm with very low birthweight. Issue 6 (31st May 2020) - South, Andrew M.; Shaltout, Hossam A.; Gwathmey, TanYa M.; Jensen, Elizabeth T.; Nixon, Patricia A.; Diz, Debra I.; Chappell, Mark C.; Washburn, Lisa K.
Abstract: Early‐life factors including preterm birth and VLBW increase the risk of hypertension, but the mechanisms remain poorly understood. Reductions in the anti‐aging protein α‐klotho are associated with hypertension, possibly due to angiotensin (Ang) II activation, but the mechanisms are incompletely understood and clinical evidence is lacking. The association of α‐klotho with the alternative Ang‐(1‐7) pathway, which counteracts Ang II to lower BP, is undescribed. We hypothesized that lower urinary α‐klotho is associated with higher BP and lower urinary Ang‐(1‐7) in preterm‐born VLBW young adults. In a cross‐sectional analysis of data from a prospective cohort of 141 preterm‐born VLBW young adults, we assessed the associations among urinary α‐klotho/creatinine, Ang II/creatinine, Ang‐(1‐7)/creatinine, Ang II/Ang‐(1‐7), and BP using generalized linear models adjusted for age and hypertensive pregnancy and conducted a sensitivity analysis in 32 term‐born young adults. Among those born preterm, lower α‐klotho/creatinine was associated with higher systolic BP (adjusted β (a β ): −2.58 mm Hg, 95% CI −4.99 to −0.17), lower Ang‐(1‐7)/creatinine (ln a β : 0.1, 0.04‐0.16), and higher Ang II/Ang‐(1‐7) (ln a β : −0.14, −0.21 to −0.07). In term‐born participants, α‐klotho/creatinine was inversely associated with Ang II/creatinine (ln a β : −0.15, −0.27 to −0.03) and Ang II/Ang‐(1‐7) (ln a β : −0.15, −0.27 to −0.03). In preterm‐born young adults with VLBW, lower urinary α‐klotho/creatinine was associated with higher SBP, lower urinary Ang‐(1‐7)/creatinine, and higher urinary Ang II/Ang‐(1‐7). Reduced renal α‐klotho expression could lead to renal Ang‐(1‐7) suppression as a novel mechanism for the development of hypertension among individuals born preterm with VLBW.